2021
DOI: 10.1002/jwmg.22094
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cumulative Effects of Climate and Development on Moose, Wolf, and Caribou Populations

Abstract: Wildlife models focused solely on a single strong influence (e.g., habitat components, wildlife harvest) are limited in their ability to detect key mechanisms influencing population change. Instead, we propose integrated modeling in the context of cumulative effects assessment using multispecies population dynamics models linked to landscape‐climate simulation at large spatial and temporal scales. We developed an integrated landscape and population simulation model using ALCES Online as the model‐building plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…We used tables of published boreal caribou range- and season-specific RSF coefficients for Ontario (Hornseth and Rempel, 2016; Rempel et al, 2021), hereafter referred to as the original RSFs. The authors referred to these models as resource selection probability functions (RSPFs), but their approach differs from what is commonly understood as an RSPF (Johnson et al, 2006) so we use the term RSF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used tables of published boreal caribou range- and season-specific RSF coefficients for Ontario (Hornseth and Rempel, 2016; Rempel et al, 2021), hereafter referred to as the original RSFs. The authors referred to these models as resource selection probability functions (RSPFs), but their approach differs from what is commonly understood as an RSPF (Johnson et al, 2006) so we use the term RSF.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of their potential limitations, RSFs and demographic models often represent the best available information to be used to support conservation decision making.. In Ontario, Canada, existing RSF (Hornseth and Rempel, 2016) and demographic models (Johnson et al, 2020) are used to support decisions provincially (Rempel et al, 2021) and federally (ECCC, 2019). These models represent the best available information for the RoF, but their utility for projecting impacts has not been formally evaluated, nor are they easy to scrutinize or apply.…”
Section: Introductionmentioning
confidence: 99%
“…By the time managers turn to predator reduction as a means to reverse the decline of caribou populations, multiple warning signals have already flashed. Even with mounting empirical evidence that confirms a relationship between habitat loss and population decline, industrial disturbance has accelerated over the past several decades since caribou declines were first documented (Environment Canada, 2012;Johnson et al, 2015Johnson et al, , 2020Nagy-Reis et al, 2021;Rempel et al, 2021;Rudolph et al, 2017). Governments have relied on piecemeal mitigation of impacts, rather than limitation of the industrial footprint, long after caribou were legally recognized as Threatened or Endangered.…”
Section: Ethical Philosophical and Social Dimensions Of Predator Mana...mentioning
confidence: 99%
“…Blakely et al (2020) reviewed RAs in Canada to understand best practices for RA and found that different approaches to regional cumulative effects assessment have emerged. Assessments that focus on thresholds to support future planning have often used the scenario modelling frameworks (e.g., ALCES Online Scenario Analysis), primarily to simulate the impacts of developments on VECs (e.g., Schneider et al, 2003;Francis and Hamm, 2011;Rempel et al, 2021). For instance, the cumulative effects assessment of the North Saskatchewan River Watershed used ALCES Online Scenario Analysis to simulate the effects of major land uses in the watershed and on watershed values over a 100-year period under four different development scenarios (Sullivan, 2009).…”
Section: Introductionmentioning
confidence: 99%